Accelerated cholesteryl ester transfer in plasma of patients with hypercholesterolemia. - Bagdade, J D (1991)
To discern the mechanism(s) that underlie abnormal cholesteryl ester transfer (CET) in patients with hypercholesterolemia, we have studied this dysfunctional step in reverse cholesterol transport in 13 subjects with genetically heterogeneous forms of hypercholesterolemia (HC). In all HC patients, the mass of CE transferred in whole plasma from HDL to VLDL and LDL increased rapidly initially and was significantly greater than in controls at 1, 2, and 4 h (P less than 0.005). To further characterize this disturbance, we performed a series of recombination experiments. Combining HC d less than 1.063 containing acceptor VLDL + LDL with the d greater than 1.063 fraction from controls containing donor HDL + CE-transfer protein (CETP) and not the converse combination showed the same characteristics of accelerated CET noted with intact HC plasma, indicating that abnormal transfer was associated with the HC acceptor lipoproteins. When HC VLDL and its subfractions and LDL were isolated separately and then combined with control d greater than 1.063 fractions, accelerated CET was only associated with VLDL1. Consistent with an acceleration of the neutral lipid transfer reaction occurring between HDL and VLDL1 in HC in vivo, we found that the triglyceride/CE ratio was decreased in HC VLDL1 (P less than 0.001), and increased in HDL (P less than 0.25). CETP mass was significantly increased in HC plasma (HC 2.3 +/- 4 micrograms/ml vs. control 1.3 +/- 0.3 micrograms/ml; mean +/- SD; P less than 0.025). This series of observations demonstrate that CET is accelerated in the plasma of HC patients, and this disturbance results from dysfunction of the VLDL1 subfraction rather than an elevation of CETP levels. Since an abnormality of this type in vivo can lead to the accumulation of potentially atherogenic CE-enriched apoB-containing lipoproteins in plasma, it may be an additional previously unrecognized factor that increases cardiovascular risk in HC patients.